Development of Electronic-Based Students’ Worksheets (E-LKPD) with Wizer.Me Application In Informatics Subject - Yuliana, Dyan; Husna, Zahra Nafilatul; Astindari, Tri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The educational process must be improved in accordance with advances in science and technology. This should be a strong motivation for educators to continue to develop their skills, especially technological skills, so that classroom learning remains relevant to the needs of today's workforce. One of them is by developing Electronic Student Worksheets (E-LKPD). The purpose of this study was to develop E-LKPD with the Wizer.me application and test its feasibility level in Informatics subjects for class X at MA Sarji Ar-Rasyid. This type of research uses the Borg and Gall R&D (Research and Development) model. The results of the study showed that the developed E-LKPD was declared feasible based on media expert validation with an average score of 94% in the